Interpreting George Town World Heritage Site Through Sensory Ethnography - Kuah, Li Feng (2021)
Following recent development in the anthropology of perception and knowledge that increasingly acknowledges the importance of multisensory experiences, this study takes a sensory ethnography approach to study people and place at George Town. George Town was inscribed as a UNESCO World Heritage Site in 2008 for its unique multicultural heritage. This study aims to offer an alternate way to conceptualise multicultural way of living in George Town as a series of multisensory correspondence. Borrowing from leading anthropologist, Tim Ingold, the concept of human correspondence is based on the understanding that when two lifelines meet or correspond to form a knot, they produce an inner feeling for each other. This inner feeling is what makes the lifelines stick together. In order to make sense of the “multicultural way of living”, this study identifies and investigates several knots of multisensory correspondence in George Town. These knots are food, festivals, language and place. By unpacking the meanings of the knots, this study reveals that the trend of multisensory correspondence in George Town is based on shared values, which is changing according to the specific given time. It is hoped that the concept of “correspondence” in this study will inspire more people-centred approaches in heritage planning and management for a sustainable future of GTWHS. Finally, following the tradition of sensory ethnography that emphasises on reflexivity, an autoethnography account is included to reflect on the ethnographer’s position in the study.